2021
DOI: 10.3390/ijms222413230
|View full text |Cite
|
Sign up to set email alerts
|

Organelle Comparative Genome Analysis Reveals Novel Alloplasmic Male Sterility with orf112 in Brassica oleracea L.

Abstract: B. oleracea Ogura CMS is an alloplasmic male-sterile line introduced from radish by interspecific hybridization and protoplast fusion. The introduction of alien cytoplasm resulted in many undesirable traits, which affected the yield of hybrids. Therefore, it is necessary to identify the composition and reduce the content of alien cytoplasm in B. oleracea Ogura CMS. In the present study, we sequenced, assembled, and compared the organelle genomes of Ogura CMS cabbage and its maintainer line. The chloroplast gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…At the full flowering stage, the newly opened flowers of the same day were removed, the petals and stamens were removed, the pollen was spread on a slide, and 2–3 drops of Alexander staining solution were added and mixed thoroughly. The slide was covered immediately, and the pollen was dyed for 3–6 h. Finally, the slides were observed under the microscope immediately after absorbing the excess liquid [ 67 ].…”
Section: Methodsmentioning
confidence: 99%
“…At the full flowering stage, the newly opened flowers of the same day were removed, the petals and stamens were removed, the pollen was spread on a slide, and 2–3 drops of Alexander staining solution were added and mixed thoroughly. The slide was covered immediately, and the pollen was dyed for 3–6 h. Finally, the slides were observed under the microscope immediately after absorbing the excess liquid [ 67 ].…”
Section: Methodsmentioning
confidence: 99%
“…Apart from a 39-bp deletion and two single-nucleotide polymorphisms (SNPs), the o rf125 and orf138 genes share 100% sequence identity with each other, which means that these two genes are highly homologous. Kos CMS caused by orf125 and Ogura CMS caused by orf138 can both be fertility restored by the fertility restorer gene Rfo / Rfk [ 114 ]. Kazama et al (2019) knocked out the mitochondrial gene orf125 by mitoTALENs in rapeseed, and the hypothesis that orf125 is the driver of Kosena-type CMS was verified, which strongly suggested that the orf138 gene is the sterility gene of Ogura CMS [ 120 ].…”
Section: Mapping and Cloning Of The Ogura Cms Genementioning
confidence: 99%